Primitive of x by Cosine of x
Jump to navigation
Jump to search
Theorem
- $\ds \int x \cos x \rd x = \cos x + x \sin x + C$
where $C$ is an arbitrary constant.
Proof 1
From Primitive of $x \cos a x$:
- $\ds \int x \cos a x \rd x = \frac {\cos a x} {a^2} + \frac {x \sin a x} a + C$
The result follows on setting $a = 1$.
$\blacksquare$
Proof 2
With a view to expressing the primitive in the form:
- $\ds \int u \frac {\d v} {\d x} \rd x = u v - \int v \frac {\d u} {\d x} \rd x$
let:
\(\ds u\) | \(=\) | \(\ds x\) | ||||||||||||
\(\ds \leadsto \ \ \) | \(\ds \frac {\d u} {\d x}\) | \(=\) | \(\ds 1\) | Derivative of Identity Function |
and let:
\(\ds \frac {\d v} {\d x}\) | \(=\) | \(\ds \cos x\) | ||||||||||||
\(\ds \leadsto \ \ \) | \(\ds v\) | \(=\) | \(\ds \sin x\) | Primitive of $\cos x$ |
Then:
\(\ds \int x \cos x \rd x\) | \(=\) | \(\ds x \sin x - \int \paren {\sin x} \times 1 \rd x + C\) | Integration by Parts | |||||||||||
\(\ds \) | \(=\) | \(\ds x \sin x - \int \sin x \rd x + C\) | simplifying | |||||||||||
\(\ds \) | \(=\) | \(\ds x \sin x - \paren {-\cos x} + C\) | Primitive of $\sin x$ | |||||||||||
\(\ds \) | \(=\) | \(\ds \cos x + x \sin x + C\) | rearranging |
$\blacksquare$
Proof 3
We have:
\(\ds \map {\dfrac \d {\d x} } {\cos x + x \sin x}\) | \(=\) | \(\ds \map {\dfrac \d {\d x} } {\cos x} + \map {\dfrac \d {\d x} } {x \sin x}\) | Sum Rule for Derivatives | |||||||||||
\(\ds \) | \(=\) | \(\ds \map {\dfrac \d {\d x} } {\cos x} + x \map {\dfrac \d {\d x} } {\sin x} + \map {\dfrac \d {\d x} } x \sin x\) | Product Rule for Derivatives | |||||||||||
\(\ds \) | \(=\) | \(\ds -\sin x + x \cos x + \sin x\) | Derivative of Cosine Function, Derivative of Sine Function, Derivative of Identity Function | |||||||||||
\(\ds \) | \(=\) | \(\ds x \cos x\) | simplifying |
Hence the result by definition of primitive.
$\blacksquare$
Warning
It is a mistake to use Primitive of Constant Multiple of Function here:
- $\ds \int x \cos x \rd x = x \int \cos x \rd x$
and thence to deduce:
- $\ds \int x \cos x \rd x = x \sin x + C$
because $x$ is not a constant in the expression $x \cos x$.